Xiphactinus audax Leidy 1870 from the Puskwaskau Formation (Santonian to Campanian) of northwestern Alberta, Canada and the distribution of Xiphactinus in North America - Vavrek, Matthew J.; Murray, Alison M.; Bell, Phil R. (Vertebrate Anatomy Morphology Palaeontology, 2016)
Xiphactinus is one of the largest teleost fish known from the Late Cretaceous of North America, and has been found across much of the Western Interior Basin. Despite extensive Late Cretaceous marine deposits occurring in Alberta, there has previously been only two possible records of Xiphactinus from the province, neither of which has been diagnosable to the species level. We describe here a portion of the lower jaws, including teeth, of Xiphactinus audax from northeast of Grande Prairie, Alberta. The fossil has large, thecodont teeth that are circular in cross section and lack any carinae, and are highly variable in their overall size. This fossil is the first diagnostic material of X. audax from Alberta, and extends the range of the species by over a thousand kilometres. During the Late Cretaceous, the area the fossil was found in was near the Arctic Circle, and represents an important datapoint within the poorly known, northern portion of the Western Interior Basin.